2017
DOI: 10.1063/1.4995281
|View full text |Cite
|
Sign up to set email alerts
|

Critical slowing down of polar nano regions ensemble in Gd3+-substituted PbMg1/3Nb2/3O3 ceramics

Abstract: Investigations on Gd-substituted lead magnesium niobate (Pb1-xGdxMg(1+x)/3Nb(2-x)/3O3; varying x = 0.01–0.1) ceramics have revealed critical slowing down of the polar nano regions (PNRs) ensemble into a “super-dipolar glass state” for higher Gd-substitution x ≥ 0.05. Low temperature electric field induced polarization switching study (P-E) has revealed a sharp decrease in the remanent polarization up to x = 0.03, which strengthen the critical slowing down of polar nano-domains dynamics, suggesting a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 67 publications
11
20
0
Order By: Relevance
“…The ε m ~ 21762 and T m ~265 K for PMN are in good agreement with earlier reports [2,6,26]. The 4 at% Gd-ion substitution in PMN has reduced the T m (~ 30 K) and ε m (~7600) and is consistent with increase in size of the CORs, decrease in number or/and sizes of the PNRs and presence of the secondary pyrochlore and GdNbO 4 phases leading to reduction in correlation among the PNRs [26,33], which is also in good agreement with earlier reports on A-site substitution by alio-valent ions [37]. The least value of the ε m ~ 4360 is observed for PGMN4-VA compared to ~ 7600 for PGMN4-VB/R, which is due to presence of ~ 48% pyrochlore phase.…”
Section: Dielectric and Ferroelectric Propertiessupporting
confidence: 92%
See 2 more Smart Citations
“…The ε m ~ 21762 and T m ~265 K for PMN are in good agreement with earlier reports [2,6,26]. The 4 at% Gd-ion substitution in PMN has reduced the T m (~ 30 K) and ε m (~7600) and is consistent with increase in size of the CORs, decrease in number or/and sizes of the PNRs and presence of the secondary pyrochlore and GdNbO 4 phases leading to reduction in correlation among the PNRs [26,33], which is also in good agreement with earlier reports on A-site substitution by alio-valent ions [37]. The least value of the ε m ~ 4360 is observed for PGMN4-VA compared to ~ 7600 for PGMN4-VB/R, which is due to presence of ~ 48% pyrochlore phase.…”
Section: Dielectric and Ferroelectric Propertiessupporting
confidence: 92%
“…The charge imbalance due to powders. Details about the ceramic fabrication are similar to the earlier report [26,31]. In all the sintered ceramics, a sintered density greater than 97% of the theoretical is achieved.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We obtain T g =211K, approach frequency f 0 =54 THz, and exponent z = 16. Here, we emphasize that a Vogel-Fulcher force-fit yields unphysical approach frequency f 0 , as also previously reported [9]; hence the VFT-model does not describe the dynamics of the system realistically.…”
Section: Introductionsupporting
confidence: 63%
“…fig. 5(e), it is clearly observed that the M''(f)relaxation peaks above 28K follow Arrhenic behaviour (T 0 =0K); with fitting parameters: f 0 =2.310 9 Hz and E a =29.2meV. Below T g =28K, relaxation peaks depict glassy behaviour with f 0 (approach frequency of dipoles) =1.110 7 Hz, E a =12.3meV, and T 0 =8K.…”
Section: Introductionmentioning
confidence: 87%